PEMBERDAYAAN MASYARAKAT DALAM MENGOPTIMALKAN POTENSI DAYA TARIK WISATA DI DESA SANGEH - I Dewa Ayu, I Dewa Ayu Sri Ratnanigsih; Ni Gusti Ayu Nyoman Srideviani; Ni Made Uttari Ivani Ardianthi; Luh Putu Dewi Framiyanti; Dwi Asri Mukaromah (Bersama : Jurnal Pengabdian Kepada Masyarakat, 2024)
ommunity Service for the Odd Semester 2023/2024 is themed'Management of Spiritual Tourism in DTW (Tourist Attraction) PenglukatanPancoran Solas Taman Mumbul, Sangeh Traditional Village, AbiansemalSubdistrict, Badung Regency.' This program aims to contribute to thedevelopment of the local community by exploring existing potential in a village.The goal is to transform these potentials into vital assets that can significantlycontribute to the community's well-being. The Real Work Lecture will beconducted in Sangeh Village. The DTW (Tourist Attraction) Penglukatan Pancoran Solas, despite itslongstanding status as a tourist destination. The primary objective is to enhance the well-being of the local community, particularly the residents in the vicinity.Various challenges have been identified in the management of DTW Penglukatan Pancoran Solas, impacting tourist visits and subsequently influencing the incomeof both the management and the local community. Addressing these challenges iscrucial for the sustainable development of the tourist attraction and the overallprosperity of the community.